Changes in the histological structure of Guerin's carcinoma in the model of tumor development on the background of diabetes mellitus - E. M. Frantsiyants; A. I. Shikhlyarova; I. V. Kaplieva; E. I. Surikova; V. A. Bandovkina; Yu. A. Petrova; I. V. Neskubina; L. K. Trepitaki; N. D. Cheryarina; V. M. Kotieva; A. A. Vereskunova; A. A. Cherkasova; et al. (Исследования и практика в медицине)
Purpose of the study. To create a model of tumor growth in the uterus in the context of diabetes mellitus (DM) and to study its morphological features.Materials and methods. The model was created using female non-linear white rats weighing 180–220 g (n = 15). Alloxan was prelim inarily injected at a dose of 150 mg/kg of weight intraperitoneally once (inducing DM). Twenty-four hours after injection, rats were anesthetized with xylazine-zolazepam, and a suspension of Guerin's carcinoma cells was transplanted into the uterine horn. Blood glucose levels, body weight, and trunk circumference were measured for two weeks. Fourteen days after transplantation, the rats were euthanized via CO₂ inhalation. The tumor affected abdominal cavity organs and uterus were then dissected, and histological sections (5–7 μm) were prepared and stained with hematoxylin and eosin staining, with a following microscopic examination.Results. At the time of tumor transplantation, the mean glucose level was 4.6 ± 0.4 mMol/L, 24 hours later it had increased to 25.4 ± 1.2 mMol/L, and it remained at this level until euthanasia. In the abdominal cavity, macroscopically, massive multinodular osseous tumor lesions of the uterus, mesentery, and internal organs were observed. Microscopically, numerous densely located cells with polymorphic hyperchromic nuclei and figures of pathological mitosis were observed, accompanied by significant vacuolization of cells that deviated from the typical characteristics of Guerin's carcinoma. Additionally, a mass of mucous elements was observed along the borders of nodules, suggestive of fringing. In the uterine tubes fused with tumor nodules, excessive mucus secretion, destruction of epithelium, and expansion of the interclavicular space were noted.Conclusion. The constructed model of orthotopic growth of Guerin's carcinoma in the rat uterus following the induction of DM by alloxan demonstrated that in a hyperglycemic environment, morphological alterations occur in both the tumor, reflecting its transition to a more aggressive mucinous low-differentiated form, and in the uterus with substantial damage to the uterine tube. Such alterations may intensify the proclivity of tumorigenesis in the uterus in the context of DM.